2018
DOI: 10.1111/jth.14297
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography is useful to distinguish acute and chronic deep vein thrombosis

Abstract: Essentials Ultrasound elastography uses tissue deformation to assess the relative quantification of its elasticity. Compression and duplex ultrasonography may be unable to correctly determine the thrombus age. Ultrasound elastography may be useful to distinguish between acute and chronic deep vein thrombosis. The exact determination of the thrombus age could have both therapeutic and prognostic implications. BACKGROUND: Background Ultrasound elastography (UE) imaging is a novel sonographic technique that is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
1
19
0
1
Order By: Relevance
“…Sample ages examined here ranged from 1 to 30 days, with an average and standard deviation of 12.2 ± 9.8 days. The average elastic modulus may also not be a good metric because of sample inhomogeneity, though similar degrees of inhomogeneity is observed for clinical scans of DVT 77 , 78 . Ultrasound images are inherently two-dimensional, and volumetric assessment of the sample stiffness may provide a more applicable comparison to bulk measurements such as mass loss.…”
Section: Discussionmentioning
confidence: 96%
“…Sample ages examined here ranged from 1 to 30 days, with an average and standard deviation of 12.2 ± 9.8 days. The average elastic modulus may also not be a good metric because of sample inhomogeneity, though similar degrees of inhomogeneity is observed for clinical scans of DVT 77 , 78 . Ultrasound images are inherently two-dimensional, and volumetric assessment of the sample stiffness may provide a more applicable comparison to bulk measurements such as mass loss.…”
Section: Discussionmentioning
confidence: 96%
“…Paper including both acute and chronic DVT used D-dimer values as a confirmation on the recent onset of acute thrombosis. 42 There is no unique accepted definition for chronic DVT, although there are sonographic characteristics that can help this classification. 43 Further research should be conducted on the usefulness of D-dimer and fibrinogen values to distinguish between acute and chronic DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Compression sonography alone would be an appropriate test when identifying proximal DVT as it can achieve an optimal specificity of 97.8%, while combined color-doppler method is the appropriate technique for identifying distal DVT (12). Ultrasound elastography (UE) can estimate elastic properties of soft tissues such as stiffness, and it has been reported that UE may be a promising technique to distinguish between acute and chronic DVT (34). However the clinical applicability of UE to DVT has not yet been fully investigated (34).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound elastography (UE) can estimate elastic properties of soft tissues such as stiffness, and it has been reported that UE may be a promising technique to distinguish between acute and chronic DVT (34). However the clinical applicability of UE to DVT has not yet been fully investigated (34).…”
Section: Discussionmentioning
confidence: 99%